Pengaruh Faktor Makroekonomi Terhadap Return Saham Bank Panin Dubai Syariah - Nabilah Haeronisa; Fifi Afiyanti Tripuspitorini; Rani Putri Kusuma Dewi (Journal of Applied Islamic Economics and Finance, 2022)
This research was conducted to determine and analyze the macroeconomic influence on returns stock at Bank Panin Dubai Syariah Tbk in Indonesia partially or simultaneously. The data used in this study is secondary data per month obtained from financial reports published by the Indonesia Stock Exchange officially on the internet site and external data in the form of reports on Bank Indonesia interest rates, inflation, and Rupiah exchange rates published by Bank Indonesia in 2015-2020 period. The type of data used is quantitative data. The analytical method used is descriptive analysis method using multiple regression equation technique. The results of the study show that simultaneously the variables of Bank Indonesia interest rates, inflation and the Rupiah exchange rate have an effect on stock returns. Partially BI interest rates have a positive effect on stock returns. Inflation partially has a positive effect on stock returns and the exchange rate has a negative effect on stock returns.